Poʻ Ūʺ sakʻ = POT - Paw Oo Thet (Takʻ Lamʻʺ Cā pe : Phranʻʹ khyi reʺ, Cā pe Loka, 1994)
Contributed articles on the life of Paw Oo Thet, 1936-1993, Burmese artist; commemorative volume brought by his friends and admirers.